Analisis Peran Rasio Profitabilitas dalam Menilai Kesehatan Keuangan Bank Tabungan Negara (BTN) - Khotimah, Retno Wahyuning Khusnul; aisyah, esy nur (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the financial health of PT Bank Tabungan Negara (BTN) for the 2019-2023 period through a profitability ratio approach. The analysis uses a quantitative descriptive method by evaluating four main profitability ratios: Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO). The data used was sourced from Bank BTN's annual financial statements. The results showed a positive trend in the bank's financial health. The analysis showed that Bank BTN experienced a significant improvement in financial health during the study period, with profitability status improving from “less healthy” to “healthy” or “fairly healthy” across various indicators. This study indicates the success of management strategies in improving the bank's operational efficiency and profitability, providing a strong foundation for sustainable growth in the future.